Aberrant alteration of follicular T helper cells in ulcerative colitis patients and its correlations with interleukin-21 and B cell subsets. Issue 10 (March 2019) - Xue, Guohui; Zhong, Yao; Hua, Lin; Zhong, Meijun; Liu, Xiaofeng; Chen, Xueli; Gao, Dian; Zhou, Nanjin
Abstract : Abstract: Patients with ulcerative colitis (UC) are at increased risk of developing colitis-associated colon cancer. Accumulating evidence suggests that follicular T helper (TFH ) cells play a crucial role in the pathogenic process of autoimmune diseases. However, little is known about the role of TFH cells in the development of UC. To investigate the role of TFH cells in the development of UC, the number of TFH cells, the level of interleukin-21 (IL-21), the numbers of B cell subsets, and clinical parameters were detected in peripheral blood from 31 UC patients and 29 healthy controls. TFH cells and the level of IL-21 were significantly higher in UC patients than in the healthy controls. A positive correlation between TFH and IL-21 cells was found in UC patients. Moreover, aberrant frequencies of different subsets of B cells were observed in UC patients, and a positive correlation was found between CD38 + CD19 + B cells and TFH cells and between CD86 + CD19 + B cells and TFH cells. A high number of TFH cells were positively associated with Mayo score, serum C-reaction protein (CRP) and serum IgG in UC patients. Our data indicate that TFH cells and IL-21 are involved in the pathogenesis of UC.